Income loss among the self-employed: Implications for individual wellbeing and pandemic policy measures - Stefan Schneck (Institut für Mittelstandsforschung (IfM) Bonn, 2021)
Due to the pandemic-induced economic crisis, self-employed individuals are currently suering considerable income losses. The self-employed and the members in their households usually form an economic unit. As a consequence, the income cuts not only aect the self-employed themselves but also the rest of their household. We used the German Socio-Economic Panel (SOEP) to calculate how much income the selfemployed are able to sacrice to achieve a subjective barely sucient household income, which we interpret as the minimum level to maintain the standard of living. Our results suggest that full-time self-employed are typically the bread-earners in their households and that, as a consequence, even moderate income losses of the self-employed often lead to problems in maintaining the living standards of their households. Conditional on individual and household characteristics, the self-employed with employees are found to live in households that are less resilient to income losses. Furthermore, a negative correlation between falling short of the barely adequate household income and wellbeing was discovered. Self-employed in households with less than adequate incomes also reported higher concerns about social cohesion. These results have implications for policy - especially in light of the economic crisis induced by the pandemic. – – Aufgrund der pandemiebedingten Wirtschaftskrise haben Selbstständige derzeit erhebliche Einkommensverluste zu beklagen. Diese Einkommenseinbußen betreffen aber nicht nur die Selbstständigen selbst, sondern auch den Rest ihres Haushalts. Vor dem Hintergrund der aktuellen Corona-Krise wurden daher Berechnungen zu den Folgen von Einkommenseinbußen im Haushaltskontext angestellt. Vollzeit-Selbstständige sind in der Regel die Hauptverdiener in ihren Haushalten, weshalb selbst moderate Einkommensverluste der Selbstständigen häufig zu Problemen bei der Aufrechterhaltung des Lebensstandards führen.
Keywords: L26; 330; entrepreneurial households; income; income cuts; self-employment